Molecular interaction between binary mixtures 1-butyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide with N-Vinyl-2-pyrrolidinone at different temperatures. (May 2017) - Suneetha, P.; Krishna, T. Srinivasa; Gowrisankar, M.; Ravindhranath, K.; Ramchandran, D.
Graphical abstract: Plots of excess molar volume, vs. mole fraction, x 1 of (a) [Bmim][NTf2] and (b) NVP, binary mixtures at temperatures, T/K = 298.15, ; At T/K = 303.15, ■; T/K = 308.15, ▲; T/K = 313.15, □; T/K = 318.15, □; T/K = 323.15, Δ. The lines represent experimental values and the markers represent values calculated from PFP theory. Highlights: New data set of density, speed of sound and refractive index data of [Bmim][NTf2 ] + NVP binary mixtures has been measured at T/K = 298.15–323.15. Excess properties of [Bmim][NTf2 ] + NVP binary mixtures discussed through molecular interactions in these mixtures. The PFP theory quantitatively correlates negative deviation V m E in the present study. Abstract: Densities ( ρ ), speeds of sound ( u ) and refractive index ( n D ) for the binary mixture of 1-Butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [Bmim] [NTf2 ] with N-Vinyl-2-pyrrolidinone (NVP) over the entire range of composition and at temperatures ranging from 298.15 K to 323.15 K at 0.1 MPa pressure, are reported in this investigation. From the experimental data, excess molar volumes ( V m E ), excess molar compressibilities ( κ s E ), excess molar isentropic compressibilities ( K s, m E ), excess speeds of sound ( u E ), and deviation in molar refraction ( Δ R m ) are calculated and fitted with Redlich-Kister polynomial smoothing equation. Excess molar volumes are predicted through PFP theory and the results are compared with experimental findings